2019
DOI: 10.18805/lr-4136
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation studies among physiological characters in Cyamopsis tetragonoloba (L.) under rainfed condition of Jaisalmer district Rajasthan, India

Abstract: The multiple plant traits associated with drought were assessed in 21 genotypes of cluster bean including check RGC-936 for their contribution to rainfed adaptation of the genotypes. All the assessed traits showed significantly different genotypic responses under rainfed conditions. Clusterbean genotypes showed wide range of variability for most of the characters and all the traits exhibited broad spectrum of ranges during both years. Total sugar content, specific leaf area at 30 and 45 DAS, number of branches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The range of variation observed for all variables in the current investigation (Table 2) revealed that there was considerable diversity among genotypes for all attributes. The similar results were reported by [9,4,3,10]. Various genetic parameters like phenotypic and genotypic co-efficient of variability (PCV, GCV), heritability, genetic advance (GA) and genetic advance as per cent of mean (GAM) for the eight characters like plant height, number pods per plant, pod length, pod girth pod weight, days to first flower, days to first harvest, pod yield per plant, have been discussed as below (Table 2 and Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The range of variation observed for all variables in the current investigation (Table 2) revealed that there was considerable diversity among genotypes for all attributes. The similar results were reported by [9,4,3,10]. Various genetic parameters like phenotypic and genotypic co-efficient of variability (PCV, GCV), heritability, genetic advance (GA) and genetic advance as per cent of mean (GAM) for the eight characters like plant height, number pods per plant, pod length, pod girth pod weight, days to first flower, days to first harvest, pod yield per plant, have been discussed as below (Table 2 and Fig.…”
Section: Resultssupporting
confidence: 92%
“…plant height (98.60%), number of pods plant (99.10%), pod length (99.60%), pod girth (95.10%), pod weight (98.40%),days to first flowering (99.30), days to first harvest (95.60) and pod yield per plant (99.60%), high heritability indicates that these characters are less influenced by environmental factors and are under the control of additive gene effects and selection for improvement of such characters would be greatly helpful in the cluster bean breeding programmes. The similar high heritability in cluster bean was reported by [12,13,10]. "GCV along with heritability estimates would provide a better picture of the amount of advance expected by phenotypic selection" [6].…”
Section: Gcv Heritability Gammentioning
confidence: 74%
“…was also drawn by Balakumbahan et al [9], in their study of 52 genotypes, it was observed that seed yield per plant were noticed to be in the range of 7.60 to 28.67, seed yield of 28.67 was recorded for Pusa Navbahar. Also, Singh et al [14], in their study recorded seed yield in the range of 7.2 -18.9 g per plant. ).…”
Section: Seed Yield Per Plantmentioning
confidence: 90%
“…Similar data was recorded byRai et al 2011, where 31 genotypes were compared, in which the number of flower cluster per plant ranged between 12.80 and 49.67, while the least number of clusters was observed in Varsha (12.80) and Pusa Navbahar (14.00). Also, Singh et al[14], in a study using 21 genotypes observed number of clusters per plant to be in a range of 8.00 to 30.70.…”
mentioning
confidence: 96%